PENGARUH GAYA KEPEMIMPINAN, KECERDASAN EMOSIONAL, DAN STRES KERJA TERHADAP PERILAKU KERJA KONTRAPRODUKTIF KARYAWAN PT HARDCASE GALERI INDONESIA - Ani Supriyani; Awan Santosa (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
This research aims to analyze the influence of leadership style, emotional intelligence, and work stress on counterproductive work behaviour of employees at PT Hardcase Galeri Indonesia. The data collection method is survey method using questionnaires. The analysis technique used is multiple linear regression. The result showed that leadership style, emotional intelligence, and work stress had a significant influence on counterproductive work behaviour.